Performance analysis of the washing machine using direct current (DC) source and alternating current (AC) source - Mohd Asri, Jusoh (Universiti Malaysia Perlis, 2009)
Nowadays, all the washing machines are operated by using alternating current (AC) source and AC motor as the operator mechanism. This project is about performance analysis of the washing machine using direct current (DC) and alternating current (AC) source. The main objective or focus more on the usage of DC motor as the new mechanism to operate the machine. This prototype will be then tested its operation and performance to compare with the current AC usage washing machine. This prototype uses two DC motor where each motor will be used for one operation, wash (also rinse) and spin. This prototype will have multifunction and buzzer. By using DC motor, the machine operations only consume 12v DC and low current usage (save electricity) and focus on renewable power source. In renewable source, the power needs to be converted to DC to be used, with the AC washing machine. But, with this prototype the source can be used directly without changing the original configuration circuit in the machine.